QTc interval prolongation in patients infected with SARS-CoV-2 and treated with antiviral drugs - Roger Esmel-Vilomara; Paola Dolader; Anna Sabaté-Rotes; Antoni Soriano-Arandes; Ferran Gran; Ferran Rosés-Noguer (Elsevier, 2022)
Introduction: Many antiviral agents, such as hydroxychloroquine, have been used to treat COVID-19, without being broadly accepted. QTc prolongation is a worrisome adverse effect, scarcely studied in pediatrics. Patients and methods: Paediatric patients affected from COVID-19 who received antivirals were matched (1:2) with controls not infected nor exposed. Electrocardiograms were prospectively analyzed at baseline, during the first 72 h of treatment and after 72 h. Results: Eleven (22.9%) out of 48 patients admitted due to COVID-19 (March-July 2020) received antiviral therapy. All had underlying diseases: congenital heart disease (4/11; 36.4%) and immunosuppression (3/11; 27.3%) stand out. 5/11 (45.5%) received treatment at baseline with a potential effect on QTc. There where no differences observed in the baseline QTc between cases and controls: 414.8 ms (49.2) vs 416.5 ms (29.4), (P = .716). Baseline long QT was observed in 2/11 cases and 2/22. Among cases, 10/11 (90.9%) received hydroxychloroquine, mainly associated with azithromycin (8/11; 72.7%), 3 received lopinavir/ritonavir and one remdesivir. The median increase in QTc after 72 h under treatment was 28.9 ms [IQR 48.7] (P = .062). 4/11 (36.4%) patients had a long QTc at 72 h, resulting in 3 patients ≥500 ms; treatment was stopped in one (QTc 510 ms) but ventricular arrhythmias were not documented. Conclusions: The use of antivirals caused an increase on the QTc interval after 72 h of treatment, being the QTc long in 36.3% of the patients, although no arrhythmic events were observed. The use of hydroxychloroquine and antivirals requires active QTc monitoring and it is recommended to discontinue treatment if QTc > 500 ms. Resumen: Introducción: Muchos antivirales, como hidroxicloroquina, se han utilizado para el tratamiento de COVID-19. La prolongación del QTc es un efecto adverso preocupante, escasamente estudiado en pediatría. Pacientes y métodos: Los pacientes pediátricos con COVID-19 que recibieron tratamiento antiviral se emparejaron (1:2) con controles no infectados ni expuestos al tratamiento. Se analizaron prospectivamente los electrocardiogramas basal, en las primeras 72 horas de tratamiento y posterior a 72 horas. Resultados: Once (22,9%) de 48 pacientes pediátricos ingresados por COVID-19 (Marzo-Julio 2020) recibieron terapia antiviral. Todos presentaban patologías de base; destacando cardiopatías (4/11; 36,4%) e inmunosupresión (3/11; 27,3%); 5/11 (45,5%) recibían tratamiento de base con potencial efecto sobre el QTc. No hubo diferencias en el QTc basal entre casos y controles: 414,8 ms (49,2) vs 416,5 ms (29,4) (P = ,716). Se observó QTc prolongado basal en 2/11 casos y 2/22 controles. De los casos, 10/11 (90,9%) recibieron hidroxicloroquina, principalmente asociada a azitromicina (8/11; 72,7%); tres recibieron lopinavir/ritonavir, uno remdesivir. La mediana de incremento del QTc tras 72 horas fue de 28,9 ms [RIC 48,7] (P = ,062); 4/11 (36,4%) presentaron un QTc largo, de los cuáles en tres ≥500 ms. En uno se paró el tratamiento (QTc 510 ms) pero no se documentaron arritmias ventriculares. Conclusiones: El uso de fármacos antivirales causó un incremento del QTc tras 72 horas de tratamiento, considerándose un QTc largo en el 36,4% de los pacientes, aunque no se objetivaron eventos arrítmicos. El uso de hidroxicloroquina y antivirales requiere monitorización activa del QTc y se recomienda suspender el tratamiento si el QTc >500 ms.